Ali novi načini zdravljenja v akutnem obdobju možganske kapi prinašajo spremembe pri rehabilitaciji bolnikov? - Goljar, Nika (Rehabilitacija (Ljubljana), 2018)
Introduction: There have been remarkable advances in acute stroke treatment in the last 15 years. The purpose of our study was to determine whether this has changed the referral of patients to the triage outpatient clinic for patients after stroke at the University Rehabilitation Institute (URI) in Ljubljana. Methods: In this retrospective study, we included patients after stroke who were first examined in our triage outpatient clinic in the period from January 1 to December 31, 2007, and from January 1, 2015, to October 31, 2015. From the available medical documentation, we collected socio-demographic data, data on the type, duration and method of treatment of the disease, the institution from which the patients were referred, the specialties of the referral physicians, and the measures set out during examination in the triage outpatient clinic. Results: Statistically significant differences in patients examined in 2015 as compared to those examined in 2007 were: longer period of time from the occurrence of stroke up to time of examination in the triage outpatient clinic (p<0.001), shorter time from outpatient examination to admission to the URI (p<0.001), higher proportion of patients who had undergone urgent fibrinolytic treatment (p<0.001), higher proportion of patients with a two-sided neurological impairment (p<0.050), lower proportion of patients sent from both University Medical Centres and higher proportion of patients arriving from regional hospitals in Slovenia (p<0.001), higher proportion of neurologists and PRM specialists among referral physicians (p<0.001), higher proportion of patients who did not meet the criteria for admission to the URI (p<0.001), and higher proportion of patients referred to the Centre for Vocational Rehabilitation. Conclusions: We believe that new treatment procedures and better organisation of health services have also changed the population of stroke patients directed to rehabilitation at our institute. We present options for further organisation of rehabilitation programmes for patients after stroke.
Keywords: methods; možganska kap; napotitev; referrals; rehabilitacija; rehabilitation; rehabilitation management; stroke; Stroke Rehabilitation; vocational rehabilitation; vodenje rehabilitacije